Isolation and characterization of uncoupler-resistant mutants of Bacillus subtilis. - Guffanti, A A (1987)
Three mutant strains of Bacillus subtilis were isolated on the basis of their ability to grow in the presence of 5 microM carbonyl cyanide m-chlorophenylhydrazone (CCCP). The mutants (AG2A, AG1A3, and AG3A) were also resistant to 2,4-dinitrophenol, and AG2A exhibited resistance to tributyltin and neomycin. The mutants all exhibited (i) elevated levels of membrane ATPase activity relative to the wild type; (ii) slightly elevated respiratory rates, with the cytochrome contents of the membranes being the same as or slightly lower than those of the wild type; (3) a passive membrane permeability to protons that was indistinguishable from that of the wild type in the absence of CCCP and that was increased by addition of CCCP to the same extent as observed with the wild type; and (4) an enhanced sensitivity to valinomycin with respect to the ability of the ionophore to reduce the transmembrane electrical potential. Finally and importantly, starved whole cells of all the mutants synthesized more ATP than the wild type did upon energization in the presence of any one of several agents that lowered the proton motive force. Studies of revertants indicated that the phenotype resulted from a single mutation. Since a mutation in the coupling membrane might produce such pleiotropic effects, an analysis of the membrane lipids was undertaken with preparations made from cells grown in the absence of CCCP. The membrane lipids of the uncoupler-resistant strains differed from those of the wild type in having reduced amounts of monounsaturated C16 fatty acids and increased ratios of iso/anteiso branches on the C15 fatty acids. Correlations between protonophore resistance and the membrane lipid compositions of the wild type, mutants, and revertants were most consistent with the hypothesis that a reduction in the content of monounsaturated C16 fatty acids in the membrane phospholipids is related, perhaps casually, to the ability to synthesize ATP at low bulk transmembrane electrochemical gradients of protons.